A disk-shaped activated carbon loaded with Bi / Bi2O3 heterojunction and its preparation method and application

By loading Bi/Bi2O3 heterojunction in chestnut shell activated carbon, combined with adsorption and photocatalytic technology, the problem of poor formaldehyde removal effect in the prior art is solved, and rapid reduction and green degradation of formaldehyde are achieved, reducing costs and improving efficiency.

CN119346100BActive Publication Date: 2025-03-25SHANGHAI HOPE TREE BIOTECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411864131.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-25
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The prior art is difficult to achieve the effect of rapidly reducing formaldehyde concentration and green degrading formaldehyde. The adsorption method has the risk of secondary release, while the photocatalytic degradation kinetics are slow and costly.

Method used

Chestnut shells were used to prepare disc-shaped activated carbon with Bi/Bi2O3 heterojunctions. By combining adsorption with photocatalytic bonding, the high specific surface area of ​​the two-dimensional activated carbon and the photocatalytic properties of bismuth/bismuth oxide heterojunctions were used to achieve rapid reduction of formaldehyde and green degradation.

Benefits of technology

The rapid reduction and green degradation of formaldehyde are achieved, which reduces the cost of catalyst preparation and improves the photocatalytic effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119346100B_ABST
    Figure CN119346100B_ABST
Patent Text Reader

Abstract

The invention discloses a disk-shaped activated carbon loaded with Bi / Bi2O3 heterojunction and its preparation method and application, the method comprising the following steps: grinding chestnut hair shell powder through 80 mesh screen, crushing and screening, facilitating carbonization, obtaining chestnut shell carbon powder; taking chestnut shell carbon powder and immersing it in 20g / L potassium hydroxide aqueous solution and stirring, then washing and drying; activating the mixture under anoxic atmosphere to obtain activated carbon powder; taking activated carbon powder, adding bismuth nitrate and 1,3,5-tris(4-carboxylphenyl)benzene, dispersing in ethanol, ultrasonic; adding the ultrasonic solution to a reactor and placing it in an oven for reaction, centrifugation after the reaction ends; after drying, the collected solid is subjected to two-stage heat treatment to obtain a disk-shaped activated carbon loaded with Bi / Bi2O3 heterojunction. The disk-shaped activated carbon loaded with Bi / Bi2O3 heterojunction according to the present invention is a two-dimensional material having both adsorption and photocatalytic degradation, which can achieve rapid reduction of formaldehyde concentration and green degradation of formaldehyde.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of formaldehyde removal, and relates to a disc-shaped activated carbon loaded with Bi / Bi2O3 heterojunction, and a preparation method and application thereof. Background Art

[0002] Formaldehyde is a colorless gas widely used in adhesives and is carcinogenic to humans. Explore efficient methods to remove formaldehyde, improve environmental air quality, and protect public health.

[0003] The adsorption method can quickly reduce the formaldehyde concentration. For example, activated carbon can be used to adsorb formaldehyde due to its abundant pores. However, most of it is physical adsorption, which makes it difficult to completely remove formaldehyde and there is a risk of secondary release.

[0004] Catalysis is a method that can completely decompose formaldehyde, among which photocatalytic degradation achieves green degradation by catalyzing the oxidation of formaldehyde into carbon dioxide and water through light excitation. However, its slow kinetics and high cost limit its application.

[0005] Therefore, there is an urgent need to develop a material that integrates coupled adsorption and catalysis, which can not only quickly reduce the formaldehyde concentration but also achieve green degradation of formaldehyde. Summary of the invention

[0006] In order to overcome the defects of the above-mentioned prior art, the present invention selects chestnut hair shell as the material for preparing activated carbon, and adds bismuth to generate disc-shaped activated carbon loaded with bismuth / bismuth oxide heterojunction, which has the following advantages: the two-dimensional activated carbon has a larger specific surface area, which can expose more abundant active sites and improve the adsorption performance; the bismuth / bismuth oxide heterojunction helps the spatial separation of electron-hole pairs and improves the photocatalytic effect; the bismuth-based material has photothermal properties, and the photothermal synergistic catalysis can not only reduce the reaction temperature of the catalysis, but also reduce the cost of catalyst preparation.

[0007] The present invention provides a disk-shaped activated carbon loaded with a Bi / Bi2O3 heterojunction, wherein the disk-shaped activated carbon loaded with a Bi / Bi2O3 heterojunction is a two-dimensional material having both adsorption and photocatalytic degradation properties.

[0008] The present invention also provides a method for preparing a disk-shaped activated carbon loaded with Bi / Bi2O3 heterojunction, the method comprising the following steps:

[0009] (1) Grind the chestnut shells and sieve them through an 80-mesh sieve to facilitate carbonization, thereby obtaining chestnut shell carbon powder.

[0010] (2) Take the chestnut shell carbon powder and immerse it in a potassium hydroxide (20 g / L) aqueous solution and stir it, then wash and dry it.

[0011] (3) Activating the mixture in an oxygen-deficient atmosphere to obtain activated carbon powder.

[0012] (4) Take the activated carbon powder, add bismuth nitrate and 1,3,5-tri(4-carboxyphenyl)benzene, disperse in ethanol, and sonicate.

[0013] (5) Add the above solution into a reactor and place it in an oven for reaction. After the reaction is completed, centrifuge and separate.

[0014] (6) After drying, the collected solid is subjected to a two-stage heat treatment to obtain a disc-shaped activated carbon loaded with Bi / Bi2O3 heterojunction.

[0015] In step (2), the volume ratio of the chestnut shell carbon powder to the potassium hydroxide solution is 1 g: 10-20 mL.

[0016] In step (2), the stirring time is 1-5 hours.

[0017] In step (2), the washing is performed by rinsing with distilled water three times.

[0018] In step (2), the drying temperature is 100°C.

[0019] In step (3), the activation temperature is 800°C.

[0020] In step (3), the activation time is 1-5h.

[0021] In step (4), the mass ratio of the activated carbon powder to bismuth nitrate is 5:1-20:1.

[0022] In step (4), the mass ratio of the activated carbon powder to 1,3,5-tri(4-carboxyphenyl)benzene is 1:1-5:1.

[0023] In step (4), the volume ratio of the activated carbon powder mass to ethanol is 1:20-1:50.

[0024] In step (4), the ultrasonic time is 1-5 hours; preferably, 1 hour.

[0025] In step (5), the reaction temperature is 150°C.

[0026] In step (5), the reaction time is 10-24 hours.

[0027] In step (5), the reactor is preferably a reactor lined with Teflon.

[0028] In step (6), the drying conditions are: drying at 80°C for 24 hours and then drying at 120°C for 24 hours.

[0029] In step (6), the two-stage heat treatment steps are: 400°C (heating rate 1°C / min) for 3 hours, and then 600°C (heating rate 5°C / min) for 4 hours.

[0030] In one embodiment, the method of the present invention comprises the following steps:

[0031] (1) The chestnut shell is cleaned, dried, and ground into powder, and then crushed and sieved through an 80-mesh sieve for easy carbonization to obtain chestnut shell carbon powder.

[0032] (2) Take the chestnut shell carbon powder and immerse it in a potassium hydroxide (20 g / L) aqueous solution while stirring. Continue stirring for a certain period of time, rinse it with distilled water three times, and dry it at 100°C.

[0033] (3) Activating the mixture at 800° C. for a certain period of time in an oxygen-deficient atmosphere to obtain activated carbon powder.

[0034] (4) Take the activated carbon powder, add bismuth nitrate and 1,3,5-tri(4-carboxyphenyl)benzene, disperse in 20 mL of ethanol, and ultrasonicate for 1 h.

[0035] (5) The above solution was added to a Teflon-lined reactor and placed in an oven at 150°C. After a certain reaction time, the sample was centrifuged from the liquid and washed five times with distilled water and ethanol respectively.

[0036] (6) Drying at 80 °C for 24 h and 120 °C for 24 h. Finally, the collected solid was subjected to a two-stage heat treatment in nitrogen, i.e., 400 °C (heating rate 1 °C / min) for 3 h and then 600 °C (heating rate 5 °C / min) for 4 h to obtain a disk-shaped activated carbon loaded with Bi / Bi2O3 heterojunction.

[0037] The present invention also provides a disk-shaped activated carbon loaded with Bi / Bi2O3 heterojunction prepared by the above method.

[0038] The present invention also provides the use of the disk-shaped activated carbon loaded with Bi / Bi2O3 heterojunction in degrading formaldehyde.

[0039] The disk-shaped activated carbon loaded with Bi / Bi2O3 heterojunction degrades formaldehyde through adsorption and photocatalysis.

[0040] The beneficial effect of the present invention is that the disc-shaped activated carbon loaded with Bi / Bi2O3 heterojunction of the present invention can not only achieve rapid reduction of formaldehyde concentration, but also achieve green degradation of formaldehyde. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1This is the SEM image of the disc-shaped activated carbon prepared in Examples 1-6.

[0042] Figure 2 Infrared camera images of the photothermal effect of the disc-shaped activated carbon prepared in Examples 2-3 and Comparative Example 1.

[0043] Figure 3 The formaldehyde removal effect of the activated carbon materials of Control Example 1 and Examples 1-6 in a light-proof environment.

[0044] Figure 4 The formaldehyde removal effect of the activated carbon materials of Control Example 1 and Examples 1-6 under full spectrum irradiation.

[0045] Figure 5 XRD of Bi / Bi2O3 and the material prepared in Example 1. DETAILED DESCRIPTION

[0046] The present invention is further described in detail with reference to the following specific examples and drawings. The process, conditions, experimental methods, etc. for implementing the present invention, except for the contents specifically mentioned below, are all common knowledge and common common sense in the art and are not particularly limited by the present invention.

[0047] The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] In all examples shown and discussed herein, any specific values ​​should be interpreted as merely exemplary and not as limiting. Therefore, other examples of the exemplary embodiments may have different values.

[0049] Embodiment 1:

[0050] (1) The chestnut shell is cleaned, dried, and ground into powder, and then crushed and sieved through an 80-mesh sieve for easy carbonization to obtain chestnut shell carbon powder.

[0051] (2) Take 1 g of chestnut shell carbon powder and immerse it in 10 mL of potassium hydroxide (20 g / L) aqueous solution while stirring. Continue stirring for 1 h, rinse with distilled water three times, and dry at 373 K.

[0052] (3) The mixture was activated at 1073 K for 1 h in an oxygen-deficient atmosphere to obtain activated carbon powder.

[0053] (4) Take 0.5 g of activated carbon powder, add 0.1 g of bismuth nitrate and 0.5 g of 1,3,5-tri(4-carboxyphenyl)benzene, disperse in 10 mL of ethanol, and ultrasonicate for 1 h.

[0054] (5) The above solution was added to a Teflon-lined reactor and placed in an oven at 150 °C. After 10 h of reaction, the sample was centrifuged from the liquid and washed five times with distilled water and ethanol respectively.

[0055] (6) Drying at 80 °C for 24 h and 120 °C for 24 h. Finally, the collected solid was subjected to a two-stage heat treatment in nitrogen, i.e., 400 °C (heating rate 1 °C / min) for 3 h and then 600 °C (heating rate 5 °C / min) for 4 h to obtain a disk-shaped activated carbon loaded with Bi / Bi2O3 heterojunction.

[0056] Embodiment 2:

[0057] (1) The chestnut shell is cleaned, dried, and ground into powder, and then crushed and sieved through an 80-mesh sieve for easy carbonization to obtain chestnut shell carbon powder.

[0058] (2) Take 2 g of chestnut shell carbon powder and immerse it in 30 mL of potassium hydroxide (20 g / L) aqueous solution while stirring. Continue stirring for 2 h, rinse with distilled water three times, and dry at 373 K.

[0059] (3) The mixture was activated at 1073 K for 1 h in an oxygen-deficient atmosphere to obtain activated carbon powder.

[0060] (4) Take 0.5 g of activated carbon powder, add 0.1 g of bismuth nitrate and 0.25 g of 1,3,5-tri(4-carboxyphenyl)benzene, disperse in 20 mL of ethanol, and ultrasonicate for 1 h.

[0061] (5) The above solution was added to a Teflon-lined reactor and placed in an oven at 150 °C. After 12 h of reaction, the sample was centrifuged from the liquid and washed five times with distilled water and ethanol respectively.

[0062] (6) Drying at 80 °C for 24 h and 120 °C for 24 h. Finally, the collected solid was subjected to a two-stage heat treatment in nitrogen, i.e., 400 °C (heating rate 1 °C / min) for 3 h and then 600 °C (heating rate 5 °C / min) for 4 h to obtain a disk-shaped activated carbon loaded with Bi / Bi2O3 heterojunction.

[0063] Embodiment 3:

[0064] (1) The chestnut shell is cleaned, dried, and ground into powder, and then crushed and sieved through an 80-mesh sieve for easy carbonization to obtain chestnut shell carbon powder.

[0065] (2) Take 1 g of chestnut shell carbon powder and immerse it in 20 mL of potassium hydroxide (20 g / L) aqueous solution while stirring. Continue stirring for 2 h, rinse with distilled water three times, and dry at 373 K.

[0066] (3) The mixture was activated at 1073 K for 4 h in an oxygen-deficient atmosphere to obtain activated carbon powder.

[0067] (4) Take 0.5 g of activated carbon powder, add 0.05 g of bismuth nitrate and 0.1 g of 1,3,5-tri(4-carboxyphenyl)benzene, disperse in 25 mL of ethanol, and ultrasonicate for 2 h.

[0068] (5) The above solution was added to a Teflon-lined reactor and placed in an oven at 150 °C. After 16 h of reaction, the sample was centrifuged from the liquid and washed five times with distilled water and ethanol respectively.

[0069] (6) Drying at 80 °C for 24 h and 120 °C for 24 h. Finally, the collected solid was subjected to a two-stage heat treatment in nitrogen, i.e., 400 °C (heating rate 1 °C / min) for 3 h and then 600 °C (heating rate 5 °C / min) for 4 h to obtain a disk-shaped activated carbon loaded with Bi / Bi2O3 heterojunction.

[0070] Embodiment 4:

[0071] (1) The chestnut shell is cleaned, dried, and ground into powder, and then crushed and sieved through an 80-mesh sieve for easy carbonization to obtain chestnut shell carbon powder.

[0072] (2) Take 1 g of chestnut shell carbon powder and immerse it in 20 mL of potassium hydroxide (20 g / L) aqueous solution while stirring. Continue stirring for 2 h, rinse with distilled water three times, and dry at 373 K.

[0073] (3) The mixture was activated at 1073 K for 5 h in an oxygen-deficient atmosphere to obtain activated carbon powder.

[0074] (4) Take 1 g of activated carbon powder, add 0.05 g of bismuth nitrate and 0.2 g of 1,3,5-tri(4-carboxyphenyl)benzene, disperse in 20 mL of ethanol, and ultrasonicate for 3 h.

[0075] (5) The above solution was added to a Teflon-lined reactor and placed in an oven at 150 °C. After 24 h of reaction, the sample was centrifuged from the liquid and washed five times with distilled water and ethanol respectively.

[0076] (6) Drying at 80 °C for 24 h and 120 °C for 24 h. Finally, the collected solid was subjected to a two-stage heat treatment in nitrogen, i.e., 400 °C (heating rate 1 °C / min) for 3 h and then 600 °C (heating rate 5 °C / min) for 4 h to obtain a disk-shaped activated carbon loaded with Bi / Bi2O3 heterojunction.

[0077] Embodiment 5:

[0078] (1) The chestnut shell is cleaned, dried, and ground into powder, and then crushed and sieved through an 80-mesh sieve for easy carbonization to obtain chestnut shell carbon powder.

[0079] (2) Take 1 g of chestnut shell carbon powder and immerse it in 20 mL of potassium hydroxide (20 g / L) aqueous solution while stirring. Continue stirring for 4 h, rinse with distilled water three times, and dry at 373 K.

[0080] (3) The mixture was activated at 1073 K for 5 h in an oxygen-deficient atmosphere to obtain activated carbon powder.

[0081] (4) Take 1 g of activated carbon powder, add 0.05 g of bismuth nitrate and 0.5 g of 1,3,5-tri(4-carboxyphenyl)benzene, disperse in 20 mL of ethanol, and ultrasonicate for 5 h.

[0082] (5) The above solution was added to a Teflon-lined reactor and placed in an oven at 150 °C. After 24 h of reaction, the sample was centrifuged from the liquid and washed five times with distilled water and ethanol respectively.

[0083] (6) Drying at 80 °C for 24 h and 120 °C for 24 h. Finally, the collected solid was subjected to a two-stage heat treatment in nitrogen, i.e., 400 °C (heating rate 1 °C / min) for 3 h and then 600 °C (heating rate 5 °C / min) for 4 h to obtain a disk-shaped activated carbon loaded with Bi / Bi2O3 heterojunction.

[0084] Embodiment 6:

[0085] (1) The chestnut shell is cleaned, dried, and ground into powder, and then crushed and sieved through an 80-mesh sieve for easy carbonization to obtain chestnut shell carbon powder.

[0086] (2) Take 1 g of chestnut shell carbon powder and immerse it in 20 mL of potassium hydroxide (20 g / L) aqueous solution while stirring. Continue stirring for 5 h, rinse with distilled water three times, and dry at 373 K.

[0087] (3) The mixture was activated at 1073 K for 5 h in an oxygen-deficient atmosphere to obtain activated carbon powder.

[0088] (4) Take 1 g of activated carbon powder, add 0.2 g of bismuth nitrate and 0.25 g of 1,3,5-tri(4-carboxyphenyl)benzene, disperse in 25 mL of ethanol, and ultrasonicate for 5 h.

[0089] (5) The above solution was added to a Teflon-lined reactor and placed in an oven at 150 °C. After 24 h of reaction, the sample was centrifuged from the liquid and washed five times with distilled water and ethanol respectively.

[0090] (6) Drying at 80 °C for 24 h and 120 °C for 24 h. Finally, the collected solid was subjected to a two-stage heat treatment in nitrogen, i.e., 400 °C (heating rate 1 °C / min) for 3 h and then 600 °C (heating rate 5 °C / min) for 4 h to obtain a disk-shaped activated carbon loaded with Bi / Bi2O3 heterojunction.

[0091] Comparative Example 1:

[0092] (1) The chestnut shell is cleaned, dried, and ground into powder, and then crushed and sieved through an 80-mesh sieve for easy carbonization to obtain chestnut shell carbon powder.

[0093] (2) Take 1 g of chestnut shell carbon powder and immerse it in 20 mL of potassium hydroxide (20 g / L) aqueous solution while stirring. Continue stirring for 5 h, rinse with distilled water three times, and dry at 373 K.

[0094] (3) The mixture was activated at 1073 K for 5 h in an oxygen-deficient atmosphere to obtain activated carbon powder.

[0095] (4) Take 1 g of activated carbon powder, disperse it in 25 mL of ethanol, and ultrasonicate for 5 h.

[0096] (5) The above solution was added to a Teflon-lined reactor and placed in an oven at 150 °C. After 24 h of reaction, the sample was centrifuged from the liquid and washed five times with distilled water and ethanol respectively.

[0097] (6) Drying at 80 °C for 24 h and 120 °C for 24 h. Finally, the collected solid was subjected to a two-stage heat treatment in nitrogen, i.e., 400 °C (heating rate 1 °C / min) for 3 h and then 600 °C (heating rate 5 °C / min) for 4 h to obtain an activated carbon control group.

[0098] Experimental results of Examples 1-6:

[0099] SEM Characterization:

[0100] The activated carbon materials prepared in Examples 1-6 of the present invention all have a disc-shaped two-dimensional structure.

[0101] XRD:

[0102] The phase structure of the obtained sample was determined by X-ray diffraction (XRD) on a HZG41B-PC x-ray diffractometer. Bi / Bi2O3 exposed (012), (104) and (110) crystal planes at 2θ=27.2°, 38.0° and 39.6°. The characteristic peaks of Bi / Bi2O3 were also retained in the material prepared in Example 1, indicating the successful preparation of the composite material.

[0103] Infrared camera test:

[0104] Under 300W full-spectrum light irradiation, an infrared camera was used to record the temperature changes of the materials prepared in Examples 2-3 of the present invention, and the initial ambient temperature was 18°C. After 1 minute of irradiation, the temperatures of the samples of Control Example 1 and Examples 2-3 of the present invention were in the range of 18.5-18.9°C, which were relatively close. After 3 minutes of irradiation, the temperature of the sample of Control Example 1 was 19.9°C, while the temperatures of the samples of Examples 2 and 3 of the present invention reached 24.5°C and 28.7°C, respectively, which illustrates the excellent photothermal effect of the composite material.

[0105] Example 7 Formaldehyde removal experiment 1:

[0106] Under light-proof conditions, the temperature and humidity in a 200L sealed cabin were controlled at 27°C and 70%, the heating table was preheated to 80°C in the cabin, 150ul of formaldehyde solution was dripped into a glass culture dish and placed on the heating table for heating for 30 minutes to completely volatilize the formaldehyde, and then 10g of samples prepared in Examples 1-6 of the present invention and Comparative Example 1 were placed, and the atmospheric sampler was used to sample at different time points, and the values ​​were recorded. Compared with Comparative Example 1, the two-dimensional activated carbon prepared in Examples 1-6 of the present invention has a better formaldehyde removal effect, with a maximum removal rate of 70%.

[0107] Example 8 Formaldehyde removal experiment 2:

[0108] Under the irradiation of 300W full-spectrum lamp, the temperature and humidity in the 200L sealed cabin are controlled at 27°C and 70%, and the heating table is preheated to 80°C in the cabin. 150ul of formaldehyde solution is dripped into a glass culture dish and placed on the heating table for heating for 30 minutes to completely volatilize the formaldehyde. Then put 10g of samples prepared by Examples 1-6 of the present invention and Comparative Example 1, and use an atmospheric sampler to take samples at different time points and record the values. Compared with Comparative Example 1, the two-dimensional activated carbon prepared by Examples 1-6 of the present invention has a maximum removal rate of 99% under light.

[0109] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0110] As used in the present invention, the term "comprising" is an open expression, that is, including the contents specified in the present invention but not excluding other contents.

[0111] As used herein, the term "and / or" includes any and all combinations of one or more of the associated listed items.

[0112] Although the embodiments of the present description have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present description, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a disk-shaped activated carbon loaded with Bi / Bi2O3 heterojunction, characterized in that: The method comprises the following steps: (1) Grinding the chestnut shells through an 80-mesh sieve for pulverization and sieving to facilitate carbonization, thereby obtaining chestnut shell carbon powder; (2) taking chestnut shell carbon powder, immersing it in a 20 g / L potassium hydroxide aqueous solution and stirring it, and then washing and drying it; (3) activating the mixture in an oxygen-deficient atmosphere to obtain activated carbon powder; (4) Take the activated carbon powder, add bismuth nitrate and 1,3,5-tri(4-carboxyphenyl)benzene, disperse in ethanol, and sonicate; (5) adding the sonicated solution into a reaction kettle and placing it in an oven for reaction, and centrifuging after the reaction is completed; the reaction temperature is 150° C.; the reaction time is 10-24 hours; (6) After drying, the collected solid is subjected to a two-stage heat treatment to obtain a disc-shaped activated carbon loaded with Bi / Bi2O3 heterojunction; the steps of the two-stage heat treatment are: heating at 400°C for 3 hours at a heating rate of 1°C / min, and then heating at 600°C for 4 hours at a heating rate of 5°C / min.

2. The method according to claim 1, characterized in that In step (2), the volume ratio of the chestnut shell carbon powder to the potassium hydroxide solution is 1 g: 10-20 mL; and / or the stirring time is 1-5 h; and / or the drying temperature is 100° C.

3. The method according to claim 1, characterized in that In step (3), the activation temperature is 800° C.; and / or the activation time is 1-5 h.

4. The method according to claim 1, characterized in that In step (4), the mass ratio of the activated carbon powder to bismuth nitrate is 5:1-20:1; and / or the mass ratio of the activated carbon powder to 1,3,5-tris(4-carboxyphenyl)benzene is 1:1-5:

1.

5. The method according to claim 1, characterized in that In step (4), the volume ratio of the activated carbon powder to ethanol is 1:20-1:50; and / or the ultrasonic treatment time is 1-5 hours.

6. The method according to claim 1, characterized in that In step (6), the drying conditions are: drying at 80°C for 24 hours and then drying at 120°C for 24 hours.

7. A disc-shaped activated carbon loaded with Bi / Bi2O3 heterojunction prepared by the method according to any one of claims 1 to 6.

8. Use of the disk-shaped activated carbon loaded with Bi / Bi2O3 heterojunction as claimed in claim 7 in the degradation of formaldehyde.

9. The use according to claim 8, characterized in that The disk-shaped activated carbon loaded with Bi / Bi2O3 heterojunction degrades formaldehyde through adsorption and photocatalysis.

Citation Information

Patent Citations

  • Mussel shell paint with indoor air purification function and preparation method thereof

    CN108129891A

  • Preparation method of chestnut shell activated carbon binary composite perfuming filter stick

    CN111972706A